How does immigration affect wages and the unemployment rate in Malaysia? a Computable General Equilibrium (CGE) approach - Said, Rusmawati; Abdul Hamid, Kamarul Hidayah; Mazlan, Nur Syazwani (Canadian Center of Science and Education, 2020)
Malaysia had approximately 2 million migrants in 2018, and this number was increasing dramatically by 25 percent in 2019. Parallels with the aims of country policy to reduce migrant workers' dependency in 2020, managing the workers needs to be clarified. At the same time, the country still needs to keep them for specific sectors. These issues motivate us to analyze the migrant worker's requirements at different levels of skills and wages. Using Computable General Equilibrium (CGE) modeling, at four-level nested CES production function, this study found high skilled migrants will harm wages for the high skilled and skilled groups while the opposite effect was observed for the semiskilled and low-skilled groups. However, when the migrant stock increases slightly below 1 percent, it will reduce the wages for semiskilled workers due to substitution effects. This study also found that the influx of low-skilled migrant workers will reduce salaries for semiskilled and low-skilled workers. The analysis also indicates that a small rise in high skilled immigrant labour will reduce the unemployment rate; likewise, increasing more than 4 percent will increase the unemployment rate. The results provide the policymaker guidelines to employ foreign workers' best skills to control the inequality of wages among skilled and low-skilled workers.